Care services in the form of personal assistance in Poland and other countries - Kowalczyk, Olga Urszula (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This article deals with personal assistance for the severely, discussing how they can lead an independent and active life, a life of their own choosing.  This kind of service has been provided since the 1980s, first in the USA and later in many countries of Europe, as well as in Australia and Canada, as a result of the international movement of Independent Living. It is an alternative to the traditional care provided by social services in residential institutions, and requires a change of thinking for the recipients of care as well as for the service providers. Needed also are appropriately designed directives to manage safety and employment. Basically none of this exists in Poland. There is an opportunity for their implementation in the new laws regarding social welfare and the existing project of 2015 in aid of dependent.